UNDERSTANDING THE AUTHOR’S INTENTION IN A TEXT - Saidova Mamura Suleymanovna; Rakhmanova Aziza Mansur qizi (Journal of new century innovations, 2024)
Annotation: The article is devoted to the role of authorization in the implementation of the author's intention in the text of a scientific work. It is shown that the formulation of the research goal determines a number of features of the manifestation of the authorization category in the text: different ratios of explicit and implicit forms of its expression, different combinations of authorization indicators with axiological operators, different nature of the relationship between authorization and the structural and logical plan of a scientific text. It is concluded that the category of authorization is one of the means of linguistic implementation of the author’s intention.